AN EVALUATION STUDY OF BILINGUAL PROGRAM IN FAWWAZ GLOBAL ISLAMIC SCHOOL YOGYAKARTA - Anita Wijayanti; Rizki Lestari; Yuyun Yulia (JELLT (Journal of English Language and Language Teaching), 2018)
The aim of this study is to describe the implementation of Bilingual Program in Fawwaz Global Islamic School Yogyakarta. It is an evaluative study implementing Context, Input, Process, and Product (CIPP) model. This research focuses on describing the implementation of bilingual education in terms of context, input, process, and product components. The subjects of this study were the English teachers, principal, and the students of Fawwaz Global Islamic School Yogyakarta during the academic year of 2016/2017. The discussion of the study is divided into four sections concerning with context, input, process and product respectively. In terms of context, this school becomes a bilingual school when it becomes a national plus school, in which one of the requirements is being able to conduct a bilingual program. For the input, the school already uses KTSP and centra system method. The school employs the entrance system using TPA and psychology test. An evaluation on the process reveals the teaching and learning processes already implement a bilingual program, but still have lots of weaknesses. In terms of product, all of the students in Fawwaz Global Islamic School Yogyakarta are able to speak English. The conclusion is this program is still open to improvement on the factor of teacher’s English capability which should be refined.